Strategi Pemberdayaan Masyarakat Inklusi Berbasis Penegakan Hukum Bagi Anak Penyandang Disabilitas Kabupaten Bandung Barat - Adibowo, Rino; Sari, Febilita Wulan; Pahlevi, Mochamad Daffa; Rachim, Rizal Aulia (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2024)
The purpose of this research is to discover concepts and strategies for inclusive community empowerment regarding children with disabilities and to discover the extent to which forms of law enforcement fulfill the rights of children with disabilities. This research was carried out descriptively analytically, namely providing existing facts, both in the form of secondary data on government materials and primary legal data. Based on these regulations, the West Bandung Regency Social Service has an important role, namely providing services in the social sector and being a solution to problems in society. The problems that exist in society are quite diverse, especially problems regarding children. This problem is an important concern for the government because cases occurring in children have increased significantly. There are various problems with children, one of which is problems with children with disabilities. In normative juridical terms, the West Bandung Regency Government already has West Bandung Regency Regional Regulation Number 2 of 2022 concerning Respect, Protection and Fulfillment of Disability Rights. Obstacles in law enforcement in fulfilling the rights of children with disabilities can be seen based on supporting infrastructure and facilities, as well as the legal culture of society. Socialization and education should be further optimized by the Social Service and other stakeholders because there is still minimal knowledge, conditions and community participation regarding disabilities. And law enforcement must involve institutions and society.